2010
DOI: 10.1086/653621
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Sialidase Fusion Protein Effectively Inhibits Human Parainfluenza Viral Infection In Vitro and In Vivo

Abstract: Background The first step in infection by human parainfluenza viruses (HPIVs) is binding to the surface of respiratory epithelial cells via interaction between viral receptor-binding molecules and sialic acid-containing receptors. DAS181, a recombinant sialidase protein containing the catalytic domain of A. viscosus sialidase, removes cell surface sialic acid, and we proposed that it would inhibit HPIV infection. Methods Depletion of sialic acid receptors by DAS181 was evaluated by lectin binding assays. Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 40 publications
4
85
0
Order By: Relevance
“…The irreversible loss of infectivity of HPIV3 virions caused by exposure to premature F-triggering agents points to the possibility of developing a new class of antivirals to combat the severe disease and high lethality associated with paramyxoviruses. We contend that both inhibition testing and mechanistic studies are likely to reflect the authentic biology if carried out in tissue resembling the natural host, and for this reason we employ the human airway epithelium model that closely reflects the in vivo behavior of HPIV3 (28) and HPIV3 antiviral molecules (47). The efficacy of the premature triggering antiviral strategy in a physiologically relevant ex vivo system that mimics the human airway supports the notion that this strategy may be useful clinically.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The irreversible loss of infectivity of HPIV3 virions caused by exposure to premature F-triggering agents points to the possibility of developing a new class of antivirals to combat the severe disease and high lethality associated with paramyxoviruses. We contend that both inhibition testing and mechanistic studies are likely to reflect the authentic biology if carried out in tissue resembling the natural host, and for this reason we employ the human airway epithelium model that closely reflects the in vivo behavior of HPIV3 (28) and HPIV3 antiviral molecules (47). The efficacy of the premature triggering antiviral strategy in a physiologically relevant ex vivo system that mimics the human airway supports the notion that this strategy may be useful clinically.…”
Section: Discussionmentioning
confidence: 88%
“…The HAE model was previously used to characterize the cell specificity of respiratory syncytial virus (45) and HPIV3 (46), studies that confirmed the model replicates those paramyxovirus-HAE interactions occurring in the human lung. We also recently employed this system to test a sialidase-based inhibitor, and showed a direct correlation between the HAE and in vivo results (47). We therefore hypothesized that peptide efficacy in this ex vivo model would correlate with in vivo efficacy.…”
Section: Compounds That Interact With the Active Site Of Hn Arementioning
confidence: 99%
“…We are developing a formulation suitable for inhalation, to deliver the antiviral agent directly to the target host tissue. We contend that a combination of an agent like Fludase, a sialidase fusion protein which interferes with receptor binding and is currently in clinical trials for adults with HPIV (28), and fusion inhibitor peptides may be a feasible combination treatment for respiratory viruses and would reduce the likelihood of eliciting resistance.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the potential for lung delivery of the lipid-conjugated HRC peptides, we used an ex vivo mucosal tissue model consisting of normal, human-derived tracheal/bronchial epithelial cells that have been cultured to form a highly differentiated model that closely resembles the human airway epithelium (HAE) tissue of the respiratory tract. We have used HAE for evaluating entry inhibitors (47)(48)(49)(50)(51). In previous work, we found that the monomeric (HRC2) and dimeric (HRC4) peptides conjugated to cholesterol both reach the basolateral face in similar concentrations (29).…”
Section: Figmentioning
confidence: 99%